EVOLUTION OF TERRORISM ACT AGAINST CIVIL AIRCRAFT - Arafah, Adhy Riadhy (UI Scholars Hub, 2014)
Since an aircraft was invented, an aircraft is not only used for transporting person from one place to another, but also can be used in war until revenge terrorism ideology and faith against a state. Furthermore, an aircraft is a representative of state where the aircraft is registered, which is also defined by terrorist as a target to attack a state. Attacking a civil aircraft is categorized as an international crime. Hereinafter, since Tokyo Convention 1960 declared, the evolution of crimes against civil aircraft has been evolved. The main target of offences is still an aircraft, however, the offence is diverted by attacking others target such as all facilitations relating to the security in civil aviation including airport and air navigation. 9/11 accident in USA is a picture how terrorism offence is still evolving. Now, aircraft and ground navigation facilitations are not the only main object in attacking by terrorist. The aircraft now is used to attack others ground target which are represented a state. The evolving of terrorism acts, in the end, is the reason why Beijing Convention 2010 on the Suppression of Unlawful Acts Relating to International Civil Aviation was made.